First measurement of the double-inclusive B/B̄ hadron energy distribution in e+e- annihilations, and of angle-dependent moments of the B and B̄ energies - Koya, A; Kenji, A; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2004)
We have made the first measurement of the double-inclusive B/B̄ energy distribution in e+e- annihilations, using a sample of 400 000 hadronic Z0-decay events recorded in the SLD experiment at SLAC between 1996 and 1998. The small and stable SLC beam spot and the CCD-based vertex detector were used to reconstruct B/B̄-decay vertices with high efficiency and purity, and to provide precise measurements of the kinematic quantities used to calculate the B energies in this novel technique. We measured the B/B̄ energies with good efficiency and resolution over the full kinematic range. We measured moments of the scaled energies of the B and B̄ hadrons vs. the opening angle between them. By comparing these results with perturbative QCD predictions we tested the ansatz of factorisation in heavy-quark production. A recent next-to-leading order calculation reproduces the data. © 2003 Elsevier B.V. All rights reserved.